PENGARUH MOTIVASI DAN DISIPLIN KERJA TERHADAP KINERJA KARYAWAN PADA PT. CIMB NIAGA JAKARTA PUSAT - Bagus Saputra; Pancagaluh Ratnasih (Journal of Research and Publication Innovation, 2025)
This research aims to analyze the influence of work motivation and work discipline on employee performance at PT. CIMB Niaga Central Jakarta. According to Andika (2019:190) "Motivation is a factor that influences human behavior, which can be called a driver, desire, support, or need. According to Siagian (2018:305) "Work discipline is the steps taken by management to encourage members organization to comply with applicable requirements", while according to Afandi (2021:83) "employee performance is the level of individual or group readiness to carry out or improve activities in accordance with their responsibilities, with results that meet expectations". Work motivation and work discipline are considered as two variables that can influence employee performance levels. This research uses quantitative methods with data collection techniques through distributing questionnaires to 95 employees. Data analysis uses validity tests, reliability tests, classical assumption tests, regression analysis, correlation coefficients, coefficients of determination and hypothesis testing. The results of this research are that motivation has a significant effect on employee performance with a coefficient of determination value of 29.3% and the hypothesis test obtained t count > t table or (6.2145 > 1.986). Work Discipline has a significant effect on employee performance with a coefficient of determination value of 40.3% and hypothesis testing obtained t count > t table or (7.919 > 1.986). Motivation and work discipline simultaneously have a significant effect on employee performance with the regression equation Y = 9.040 + 0.200X1 + 0.367X2. The coefficient of determination value is 46.3% while the remaining 55.7% is influenced by other factors. Hypothesis testing obtained a calculated F value > F table or (39.616 > 2.700).